Comparison of Information Representation Formalisms for Scalable File Agnostic Information Infrastructures - Kryza, Bartosz; Kitowski, Jacek (Computing and Informatics, 2015)
In the early days of computing, files where just a natural way of storing information – which reflected the way one would file their punch cards in a cabinet drawer. Unfortunately, the requirement to fragment information into such chunks, is a huge bottleneck for the evolution of global information space that the Internet has become. The concept of file causes several problems including unnatural clustering of information, unnecessary replication of data and very expensive information discovery in distributed computing environments. The overall goal of this work is to design an architecture enabling new era in computing and networking – a computing infrastructure without the concept of file. Files are seen by many specialists as one of the main bottlenecks of modern IT systems evolution. This is mostly due to a very unnatural fragmentation of information into chunks which are easier to manage by operating systems but much more difficult for information processing tools and eventually by humans themselves.